A Case Manager's Resilient Reality. Issue 5 (September 2021) - Powell, Suzanne K.
Abstract : Case managers are a ubiquitous group of professionals whom others rely upon when times are difficult. October 10–16, 2021, is National Case Management Week. Although 2020 tested us to the core, we can celebrate our week with pride and satisfaction.